The Effect of Benson Relaxation Therapy on Anxiety and the Quality of Sleep Among Preeclamptic Women - Roma, Naglaa Zaki Hassan; Alam, Tahany Hassan Mohamed; Hables, Reda Mhmoud Mohamed; Nakeb, Mayar Ezzeldeen El (International Journal For Research In Health Sciences And Nursing, 2020)
Background: Pre-eclampsia (PE) a syndrome that occurs during pregnancy that results in real risk and a signiﬁcant impact on indicators related to maternal and child physical and psychological health. Therefore, this study aimed to investigate the effect of Benson relaxation therapy on anxiety and the quality of sleep among pre-eclamptic women. A non-randomized controlled clinical trial research design was used. A simple random sample of 80 pre-eclamptic women were randomly divided into two equal groups, namely; study group and control group were chosen from El-Shatby Maternity University Hospital in eclamptic and intensive care unit. Tools of the study: three tools were used: (1) The socio-demographic and antenatal profile questionnaire, (2) Beck Anxiety Inventory (BAI) (3) The Groningen Sleep Quality Scale (GSQS). Results: The study results revealed a highly statistically significant difference between the study and control groups in relation to decrease their anxiety and increase their quality of sleep after the intervention (p=0.001). Also, the anxiety was negatively correlated was quality of sleep. Conclusion: Benson relaxation can be used as an effective intervention to decrease anxiety and improve the quality of sleep. Recommendation: Benson relaxation technique is an effective intervention for pre-eclamptic women and thus should be included in the nursing care plan of this group of pregnant women.